MEDIA DEVELOPMENT OF LIFE CYCLE DIAGRAMS OF LIVING THINGS FOR CLASS IV PRIMARY SCHOOL STUDENTS - Lestari, Kurnia Dwi; Mujiwati, Endang Sri; Putri, Kharisma Eka (Universitas Labuhanbatu, 2023)
Abstract In science learning material on animal life cycles in class IV SDN Tarokan 3, the teacher has not used learning media. In the learning process the teacher uses the lecture method which causes students to be less active. This has an impact on students' lack of understanding of animal life cycle material which results in more than 50% of students getting learning outcomes below the KKM. This research aims to (1) determine the validity of life cycle material diagram media products for living creatures for fourth grade elementary school students, (2) determine the effectiveness of living creature life cycle material diagram media products for fourth grade elementary school students, and (3) determine the practicality media product diagram material on the life cycle of living things for fourth grade elementary school students. The research model used is research and development (R&D). Based on this research, the results were: (1) the life cycle diagram media for living creatures was declared very valid with a percentage of 92.05%; (2) the life cycle diagram media for living creatures was declared very effective with a classical completion percentage of 90% in limited trials and 95% in extensive trials; and (3) the media for life cycle diagrams of living things is stated to be very practical with a teacher response percentage of 98.6%, student percentage gains in limited trials of 99.5% and student responses in extensive trials of 99.5%, so that the media can be said to be valid , effective, complete, and influential in improving student learning outcomes. Based on the results of this research, it was concluded that the media for life cycle diagrams of living creatures is valid and suitable for use as learning media for fourth grade elementary school students. Abstrak Pada pembelajaran IPA materi siklus hidup hewan kelas IV SDN Tarokan 3 guru belum menggunakan media pembelajaran. Dalam proses pembelajaran guru menggunakan metode ceramah yang menyebabkan siswa kurang aktif. Hal ini berdampak pada pemahaman siswa kurang terhadap materi siklus hidup hewan yang mengakibatkan lebih dari 50% siswa mendapatkan hasil belajar di bawah KKM. Penelitian ini bertujuan untuk (1) mengetahui kevalidan produk media diagram materi siklus hidup makhluk hidup untuk siswa kelas IV Sekolah Dasar, (2) mengetahui keefektifan produk media diagram materi siklus hidup makhluk hidup untuk siswa kelas IV Sekolah Dasar, dan (3) mengetahui kepraktisan produk media diagram materi siklus hidup makhluk hidup untuk siswa kelas IV Sekolah Dasar. Model penelitian yang gunakan yaitu penelitian pengembangan atau Research and Development (R&D). Berdasarkanpenelitian ini mendapatkan hasil (1) media diagram siklus hidup makhluk hidup dinyatakan sangat valid dengan presentase 92,05%; (2) media diagram siklus hidup makhluk hidup dinyatakan sangat efektif dengan presentase ketuntasan klasikal 90% pada uji coba terbatas dan 95% pada uji coba luas; dan (3) media diagram siklus hidup makhluk hidup dinyatakan sangat praktis dengan presentase respon guru 98,6%, perolehan presentase siswa pada uji coba terbatas 99,5% dan respon siswa pada uji coba luas 99,5%, sehingga media dapat dikatakan valid, efektif, tuntas, dan berpengaruh dalam meningkatkan hasil belajar siswa. Berdasarkan hasil penelitian tersebut disimpulkan bahwa media diagram siklus hidup makhluk hidup valid dan layak digunakan sebagai media pembelajaran untuk siswa kelas IV sekolah dasar.Kata kunci:Pengembangan, Media Diagram Siklus Hidup Makhluk Hidup, Pembelajaran IPA